Konflik Sosial dan Alternatif Pemecahannya - Parsudi Suparlan (Antropologi Indonesia, 2006)
In this article the author looks into social conflict and alternative solutions to the problem. He begins by discussing the merits of a conflict model in viewing society, as expounded by Dahrendorf, Bailey and others. The author argues that, in contrast, the New Order Regime of Indonesia followed a model of equilibrium, characteristic of most pseudo-democratic or authoritarian states. With an emphasis on gotong royong. uniformity, balance and harmony, any move toward individuality or anti-stability was seen as having no function in the maintenance of the system. Holding to this latter model, any view deviating from official policy was removed. Different views could only be expressed by those with power, who were in fact those in power. By setting the rules of the game, their own views were never seen as a form of deviation. This led to the emergence of conflict between various groups, whereby some were stripped of their identities, dignity and/or material resources in the interest of the state or more powerful groups. Conflicts between ethnic groups present a special problem, because any attack on the group is seen as an attack on the individual, and vice versa. The author suggests that with a conflict model, differences are a given, and conflicts give rise to competition where there exist rules for competition that are fair and well-enforced. These rules must be enforced by an impartial police. However, the incorporation of the police into the Indonesian military for the past 32 years has placed emphasis on the use of military tactics for resolving conflict. In fact, one solution to the problem of conflict is the presence of one institution or organization that can be trusted and depended upon by all parties involved; and this should be the police.Key words: conflict potentiality; ethnic plurality; culture dominant.